Implantação da análise de perigos e pontos críticos de controle no processamento do leite pasteurizado Tipo A - Tobias, Wanderléia [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Hazard Analysis and Critical Control Points (HACCP) is one of the main tools currently used to ensure safety, quality and integrity of foods. In Brazil, the government agency responsible for the regulation and standardization of services linked to the agricultural sector has been engaged in making milk industries to accomplish the system deployment. So, the aim of this study was to implement the HACCP program in the processing of pasteurized grade A milk. First of all, it was applied a checklist to assess on the level of the pre requisites programs used in the routine activities of the dairy industry. The results were used as references for the adaptation of the industry to the legislation and for the development of the HACCP system. The Critical Control Points (CCP) were identified with a “decision tree” protocol. No physical or chemical CCP were identified, whereas pasteurization and packaging were considered biological CCP since a failure on these steps might result in unacceptable microbial counts in the final product. For these CCP, the preventive and corrective measures, critical and safety limits and procedures for monitoring and checking were established. The implementation of the HACCP for the processing of grade A pasteurized milk successfully controlled the biological hazards, enabled the product to achieve bacterial counts fewer than 103 C.U.F./mL and so made the industry to meet legal requirements and ensure safety for its product
Keywords: Tecnologia de alimentos; Segurança alimentar; Culinária; Alimentos - Legislação; Alimentos - Consumo; Food handling